Pemodelan Hurdle Poisson Regresion pada Jumlah Kasus Kematian Akibat Penyakit HIV/AIDS di Provinsi Jawa Barat - Adinda Zahrotul Rizkiah; Nusar Hajarisman (UNISBA Press, 2023)
Abstract. To model discrete data related to Poisson events, one way is to use Poisson Regression. If a data contains many zero values, the data can experience overdispersion. This overdispersion problem will increase type I errors, to model the overdispersion data, Hurdle Poisson Regression modeling is needed. Transmission of HIV/AIDS is caused by receiving HIV positive blood donors, through the mother's placenta to her fetus, and sexually transmitted infections. AIDS causes the human body's ability to fight infection to disappear, which can lead to someone's death. However, AIDS-related deaths do not always occur, especially in the districts/cities of West Java Province. So it is necessary to model Hurdle Poisson Regression in cases of death from AIDS. Data obtained through the official website of Open Data Jabar. The processed data includes: Number of AIDS-related Death Cases (Y), Number of HIV Positive Blood Donor Cases (X1), and Number of Syphilis Disease Cases (X2). Based on the research results, two models were formed, for the truncated model and for the logit model, but in the truncated model, HIV Positive Blood Donors (X1) and Syphilis Disease Cases (X2) have an effect on Death Cases due to AIDS in West Java Province, while in the logit model is only Cases of Syphilis (X2) which affect Cases of AIDS-related Deaths in West Java Province. Abstrak. Untuk memodelkan data diskrit yang menyangkut pada kejadian Poisson, salah satunya ialah menggunakan Regresi Poisson. Apabila suatu data mengandung banyak nilai nol, data tersebut dapat mengalami overdispersi. Permasalahan overdispersi ini akan memperbesar kesalahan jenis I, untuk memodelkan data yang mengalami overdispersi tersebut perlu pemodelan Hurdle Poisson Regression. Penularan HIV/AIDS disebabkan oleh penerimaan donor darah positif HIV, melalui plasenta Ibu ke janinnya, dan Penyakit Infeksi Menular Seksual. AIDS menyebabkan kemampuan tubuh manusia untuk melawan infeksi hilang, sehingga dapat menyebabkan kematian seseorang. Akan tetapi kematian akibat AIDS tidak selalu terjadi khususnya di Kabupaten/Kota Provinsi Jawa Barat. Maka perlu pemodelan Hurdle Poisson Regression pada kasus kematian akibat AIDS ini. Data diperoleh melalui website resmi Open Data Jabar. Data yang diolah tersebut antara lain: Jumlah Kasus Kematian Akibat AIDS (Y), Jumlah Kasus Donor Darah Positif HIV ( ), dan Jumlah Kasus Penyakit Sifilis ( ). Berdasarkan hasil penelitian dimana terbentuk dua model, yakni untuk model truncated dan untuk model logit. Akan tetapi pada model truncated, Donor Darah Positif HIV ( ) dan Kasus Penyakit Sifilis ( ) berpengaruh terhadap Kasus Kematian akibat AIDS di Provinsi Jawa Barat, sedangkan pada model logit hanya Kasus Penyakit Sifilis ( ) yang berpengaruh terhadap Kasus Kematian akibat AIDS di Provinsi Jawa Barat).